Antibacterial Activities of Glycyrrhiza gabra Linn. (Licorice) Root Extract against Porphyromonas gingivalis rand Its Inhibitory Effects on Cysteine Proteases and Biofilms - Suwannakul, Suttipalin; Chaibenjawong, Plykaeow (UI Scholars Hub, 2017)
Little is known about the antibacterial activity of licorice root extract. Objective: To investigate the antimicrobial and anti-proteolytic activities of root extract on Porphyromonas gingivalis in both planktonics and biofilm cells. Methods: Glycyrrhiza glabra (G. glabra) roots were extracted by 95% ethanol freeze dried and kept at -20˚C prior experiments. P.gingvalis (ATCC 33277) were cultured and used for experiments. Determination of antibacterial activities of G.glabra extracts (lico rice) against P.gingvalis planktonic the MIC and MBC were evaluated by agar well diffusion, broth microdilution, and time-killing methods. The crystal violet assay was used to assess the biofilm growth inhibition and the disruption of established biofilm. The Arg - specific proteolytic activities were analyzed using the chromogenic substrates assays using N-benzoyl-DL-arginine-4-nitroanilide hydrochloride and N-(p-tosyl)-Gly-Pro-Lys 4-nitroanilide acetate salt to assess the enzymatic inhibition effects of the extracts com¬pared with the controls. Results: The licorice root extract had antimicrobial activities on P.gingivalis with MIC and MBC of 62.5μg/ml and 25 μg/ml respectively. The assay showed that Licorice root extronidazole. Licorice root extract also had effect on P.gingivalis biofilms. Quantification by crystal violate staining showed the reduction of bioflm mass in the presence of Licorice root extract. The Arg-and Kgp- proteases activities were also inhibited by the extract in dose dependent manner. Conclusion: The results suggested that licorice root extract may has poten¬tial therapeutics values as a candidate for periodontal disease.